2003
DOI: 10.1128/aem.69.8.4689-4696.2003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Rhodosporidium toruloides Strain DBVPG 6662 on Dibenzothiophene Crystals and Orimulsion

Abstract: Strains DBVPG 6662 and DBVPG 6739 of Rhodosporidium toruloides, a basidiomycete yeast, grew on thiosulfate as a sulfur source and glucose (2 g liter ؊1 or 10.75 mM) as a carbon source. DBVPG 6662 has a defective sulfate transport system, whereas DBVPG 6739 barely grew on sulfate. They were compared for the ability to use dibenzothiophene (DBT) and related organic sulfur compounds as sulfur sources. In the presence of glucose as a carbon source and DBT as a sulfur source, strain DBVPG 6662 grew better than DBVP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
1
12
0
3
Order By: Relevance
“…The ascomycetous yeast Candida digboiensis has been shown to desulfurise the heterocyclic organosulfur compound dibenzothiophene (DBT), although it not known whether this yeast can utilize DBT as its sole source of sulfur (Sood & Lal, 2009). Strains of the basidiomycetous yeast Rhodosporidium toruloides can utilize DBT as the sole sulfur source by directly adhering to the surface of DBT crystals in solution (Baldi et al, 2003). A number of studies have demonstrated the ability of lignindegrading fungi to desulfurise DBT and various other heterocyclic organosulfur compounds such as diphenylsulfide and thianthrene (Faison et al, 1991;Ichinose et al, 2002;Van Hamme et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The ascomycetous yeast Candida digboiensis has been shown to desulfurise the heterocyclic organosulfur compound dibenzothiophene (DBT), although it not known whether this yeast can utilize DBT as its sole source of sulfur (Sood & Lal, 2009). Strains of the basidiomycetous yeast Rhodosporidium toruloides can utilize DBT as the sole sulfur source by directly adhering to the surface of DBT crystals in solution (Baldi et al, 2003). A number of studies have demonstrated the ability of lignindegrading fungi to desulfurise DBT and various other heterocyclic organosulfur compounds such as diphenylsulfide and thianthrene (Faison et al, 1991;Ichinose et al, 2002;Van Hamme et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados obtidos do fracionamento geoquímico demonstram, de forma clara, que a condição de redução proporcionou a redução dos teores de bário das frações mais estáveis (F2 e F4) e aumento na fração de maior labilidade (F1), aumentando o risco de contaminação ambiental. 10,31,32 Não há diferença significativa entre os teores de bário lixiviados nos diferentes pontos de coleta, ou seja, cada volume coletado dentro de cada dose ( Figura 1S, material suplementar), apresentando uma tendência de se manter, praticamente, constante entre o primeiro e o último volume coletado. Esse comportamento é, provavelmente, devido à baixa solubilidade do sulfato de bário (K ps = 1,1 x 10 -10 mol L -1 ) e ao equilíbrio químico do elemento em solução.…”
Section: Figura 1 Valores De Potencial De Oxirredução (Eh) Para Doisunclassified
“…Diversos trabalhos evidenciam que em solos com valores baixos de Eh (< -220 mV) e na presença de BaSO 4, bactérias redutoras de sulfato são responsáveis pela solubilização e aumento do bário em solução. 10,34,35 A Figura 3 apresenta a quantidade de bário removido por cada volume coletado no lixiviado e o total removido em função das doses aplicadas e níveis de umidade. A remoção de bário ocorreu de forma diferenciada, principalmente, em função das doses aplicadas e aumentaram de forma significativa e linear.…”
Section: Figura 1 Valores De Potencial De Oxirredução (Eh) Para Doisunclassified
See 1 more Smart Citation
“…Thus, DBT has been as a model compound in desulfurization studies (Okada et al 2002a, b). Considering progress of biological reactions in mild conditions and inexpensiveness of microbial fermentation processes, Biocatalytic desulfurization (BDS) has been a main candidate as an alternative or complement desulfurization process (Baldi et al 2003;Gupta and Roychoudhury 2005;Lee et al 1995). Many studies have used traditional and the same techniques to detect DBT desulfurizing and/or degrading microorganisms by enrichment in aquatic systems and metabolic pathways have been elucidated for some of them (Baldi et al 2003;Gupta and Roychoudhury 2005;Kropp et al 1997;Okada et al 2002a, b;Rashidi et al 2006;Soleimani et al 2007).…”
Section: Introductionmentioning
confidence: 99%